Complete chloroplast genome sequence of Betula microphylla (Betulaceae) - Donglai Hua; Jianbo Zhu (Mitochondrial DNA. Part B. Resources, 2020)
Betula microphylla (Betulaceae) is a species widely distributed in Xinjiang China and in Mongolia and Siberia of Russia. In this study, we described the complete chloroplast genome of B. microphylla based on Illumina paired-end sequencing. The chloroplast genome of B. microphylla is 160,489 bp long, including two inverted repeats (IRs, 26,070 bp), separated by a large single-copy region (LSC, 89,306 bp), and a small single-copy region (SSC, 19,045 bp). The overall GC content of the whole genome is 36.1%, and the corresponding values of the LSC, SSC, and IR regions are 33.7%, 29.7%, and 42.5%. The phylogenetic analysis indicated that B. microphylla is closely related to Betula occidentalis.